Proporcionalidade e regra de três: um olhar sobre o teorema fundamental da proporcionalidade - SILVA , Fabiano Calacio (2021)
In this work we have as main objectives to show the concept of reason, proportion and the Fundamental Proportionality Theorem, employing methods as a simpler and more didactic way of doing direct, inverse and mixed proportional division, as well as a strategy of using the Fundamental Theorem of Proportionality for the resolution of three simple and compound rule problems. At the end of the work, the results and conclusions are highlighted with applications.